New Dimensional Staging of Bisphosphonate-Related Osteonecrosis of the Jaw Allowing a Guided Surgical Treatment Protocol: Long-Term Follow-Up of 266 Lesions in Neoplastic and Osteoporotic Patients from the University of Bari. (5th June 2014) - Franco, Simonetta; Miccoli, Simona; Limongelli, Luisa; Tempesta, Angela; Favia, Giorgio; Maiorano, Eugenio; Favia, Gianfranco
Abstract : Bisphosphonate-related osteonecrosis of the jaw (BRONJ) is the most serious side effect in patients receiving bisphosphonates (BPs) for neoplastic disease and osteoporosis. The aim of this study is to propose a new dimensional stage classification, guiding the surgical treatment of BRONJ patients, and to evaluate the success rate of this new management. From 2004 to 2013, 203 neoplastic and osteoporotic patients with 266 BRONJ lesions were referred to the Odontostomatology Unit of the University of Bari. All patients underwent surgery after suspension of BPs therapy and antibiotic treatment. The surgical procedure was complemented by piezosurgery and followed by the application of hyaluronate and amino acids. The new dimensional staging suggests the choice of the surgical approach, and allows the prediction of postoperative complications and soft and hard tissues healing time, guiding the surgical treatment protocol. This protocol could be a successful management strategy for BRONJ, considering the low recurrences rate and the good stabilisation of the surgical sites observed after a long-term follow-up.